Studies on Steinschneider: Moritz Steinschneider and the emergence of the science of Judaism in nineteenth-century Germany - Leicht, Reimund; Freudenthal, Gad (Studies in Jewish history and culture, 2012)
Preliminary Material /Reimund Leicht and Gad Freudenthal --A Jewish Scholar in Nineteenth-Century Europe Moritz Steinschneider: /Ismar Schorsch --"Your Loving Uncle": /Michael L. Miller --Leopold Zunz and Moritz Steinschneider: /Céline Trautmann-Waller --Moritz Steinschneider's Notion of Encyclopedias /Arndt Engelhardt --From Dialektik to Comparative Literature: /Irene E. Zwiep --Moritz Steinschneider's Concept of the History of Jewish Literature /Reimund Leicht --Moritz Steinschneider and the Noble Dream of Objectivity /Nils Roemer --The Aim and Structure of Steinschneider's Die Hebraeischen Übersetzungen des Mittelalters. The Historiographic Underpinnings of a Masterpiece and Their Untoward Consequences /Gad Freudenthal --Steinschneider and the Irrational: /Giulio Busi --Steinschneider's Interstitial Explanation of Magic /Giuseppe Veltri --The Father of Hebrew Bibliography Moritz Steinschneider and the Discipline of 'Hebrew Manuscripts Study' /Judith Olszowy-Schlanger --Moritz Steinschneider and the Leiden Manuscripts /Jan Just Witkam --Creating a New Literary Genre: /Steven Harvey and Resianne Fontaine --Steinschneider's Manuscripts /Benjamin Richler --Aron Freimann and the Development of Jewish Bibliography in Germany in the 20th Century /Rachel Heuberger --A Living Citizen in a World of Dead Letters: /Avriel Bar-Levav --The Study of Medieval Literature, Philosophy and Science Moritz Steinschneider and Karaite Studies /Daniel J. Lasker --Moritz Steinschneider's Contribution to Judaeo-Arabic Studies /Paul B. Fenton --Steinschneider and Yiddish /Diana Matut --Steinschneider and Italy /Asher Salah --Mathematik bei den Juden, cent ans après /Tony Lévy --Steinschneider as Historian /Norman Golb --Moritz Steinschneider in Contemporary Research The Genesis of Die Hebraeischen Übersetzungen des Mittelalters /Charles H. Manekin --Genizat Germania. A Projected Comprehensive Electronic Catalogue of Hebrew Fragments Extracted from Bindings of Books or Archival Files in German Libraries and Archives /Elisabeth Hollender and Andreas Lehnardt --Documents and Texts Tracing Steinschneider in the Berlin Staatsbibliothek /Petra Figeac --Der Aberglaube [1900] /Moritz Steinschneider --Index /Reimund Leicht and Gad Freudenthal.